1998
DOI: 10.1111/j.2042-7158.1998.tb06169.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Mechanism of Flux Across Polydimethylsiloxane Membranes by use of Quantitative Structure-Permeability Relationships

Abstract: Quantitative structure-permeability relationships (QSPRs) based on readily calculated parameters have been developed to study penetration across a polydimethylsiloxane membrane. Maximum steady-state flux values for 256 compounds through a polydimethylsiloxane membrane were taken from previous studies. Forty-three physicochemical parameters were calculated for each compound and their significance to flux determined. Removal of fourteen outliers enabled derivation of a significant three-parameter QSPR based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…Moss et al reported that silicone membrane permeability is essentially different from that of human skin. 19,20) The log K o/w of the model compounds showed wide lipophilicity range from 0.84 to 5.36. On the other hand, in the present study, significance correlations of permeation parameters between silicone membrane and human or animal skin in the lipophilicity range of 0.5≤log K o/w ≤3.5 of model compounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moss et al reported that silicone membrane permeability is essentially different from that of human skin. 19,20) The log K o/w of the model compounds showed wide lipophilicity range from 0.84 to 5.36. On the other hand, in the present study, significance correlations of permeation parameters between silicone membrane and human or animal skin in the lipophilicity range of 0.5≤log K o/w ≤3.5 of model compounds.…”
Section: Discussionmentioning
confidence: 99%
“…17,18) However, it also has been reported that silicone membrane permeability is essentially different from human skin permeability, 19,20) and it is unclear if silicone membranes were effective as an alternative to human or animal skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies by AgatonovicKustrin et al and Cheng et al have published on use of ANNs in determining the quantitative structure-permeability relationship of penetration across skin or polydimethylsiloxane membranes as the model of skin permeation [123][124][125][126]. A set of over 200 compounds and their maximum steady state flux was collected from the literature [127,128]. In Agatonovic-Kustrin et al study, twelve of 42 molecular descriptors were selected for ANN modeling of maximum steady-state flux by the use of genetic algorithm, that include molecular shape and size, inter-molecular interactions, hydrogen-bonding capacity of drugs, and conformational stability [123].…”
Section: Prediction Permeability Of Skin and Blood Brain Barriermentioning
confidence: 99%
“…In recent years there has been increasing attention paid to the problem of predicting the rate at which a substance will pass through human skin [1][2][3][4][5][6]. Interest in this issue has been driven by the pharmaceutical industry, where it is important to be able to predict the rate at which a drug will pass through the skin and into the bloodstream.…”
Section: Introductionmentioning
confidence: 99%